2022
DOI: 10.1002/ajmg.a.62764
|View full text |Cite
|
Sign up to set email alerts
|

NAD+ deficiency in human congenital malformations and miscarriage: A new model of pleiotropy

Abstract: Pleiotropy is defined as the phenomenon of a single gene locus influencing two or more distinct phenotypic traits. However, nicotinamide adenine dinucleotide (NAD+) deficiency through diet alone can cause multiple or single malformations in mice. Additionally, humans with decreased NAD+ production due to changes in pathway genes display similar malformations. Here, I hypothesize NAD+ deficiency as a pleiotropic mechanism for multiple malformation conditions, including limb-body wall complex (LBWC), pentalogy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…There is growing recognition that the phenotypic diversity in VACTERL association might be more extensive than previously believed (Husain et al, 2018). Furthermore, several authors have noted an overlap between recurrent malformation associations including VACTERL and OAVS (Adam et al, 2020; Duncan & Shapiro, 1993; Mark, 2022). Adam et al (2020) proposed re‐conceptualizing this group of disorders, introducing the term “recurrent constellations of embryonic malformations” (RCEM), acknowledging the phenotypic overlap, and suggesting shared pathogenesis (Adam et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is growing recognition that the phenotypic diversity in VACTERL association might be more extensive than previously believed (Husain et al, 2018). Furthermore, several authors have noted an overlap between recurrent malformation associations including VACTERL and OAVS (Adam et al, 2020; Duncan & Shapiro, 1993; Mark, 2022). Adam et al (2020) proposed re‐conceptualizing this group of disorders, introducing the term “recurrent constellations of embryonic malformations” (RCEM), acknowledging the phenotypic overlap, and suggesting shared pathogenesis (Adam et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have also implicated nicotinamide adenine dinucleotide (NAD) deficiency as a potential underlying mechanism in these RCEM‐shared pathways, highlighting the pleiotropic effects of NAD deficiency on organ system development (Mark, 2022). Shi et al (2017) reported the first four patients with pathogenic biallelic variants in genes in the NAD de novo synthesis pathway.…”
Section: Discussionmentioning
confidence: 99%
“… Adapted from Shi et al, 2017, Szot et al, 2020, Ehmke et al, 2020, Schüle et al, 2021, Szot et al, 2021, L. Bird, personal communication, September 14, 2021, Mark, 2022, Kortbawi et al, 2022. …”
Section: Introductionmentioning
confidence: 99%
“…There is considerable overlap in anomalies between some multiple malformation conditions (Adam et al, 2020). In a recent article, NAD+ deficiency is hypothesized as a pleiotropic mechanism for multiple malformation conditions, including limb‐body wall complex (LBWC), pentalogy of Cantrell (POC), omphalocele‐exstrophy‐imperforate anus‐spinal defects (OEIS) complex, VACTERL association, oculoauriculovertebral spectrum (OAVS), Mullerian duct aplasia‐renal anomalies‐cervicothoracic somite dysplasia (MURCS), sirenomelia, and urorectal septum malformation (URSM) sequence, along with miscarriages and other forms of congenital malformation (Mark, 2022). Moreover, conditions with overlapping anomalies are also associated with environmental risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Van Allen and colleagues proposed that the wide range of anomalies affecting different organ systems are due to a vascular disruption event in week 4 to week 6 of gestation (Van Allen et al, 1987). Several other theories have been proposed, among which are the occurrence of both intrinsic and extrinsic factors, a disturbance of the embryonic folding process related to a malfunctioning of the body wall ectodermal placode (Hartwig et al, 1989), a primary defect of the ectoderm of the embryonic disc (Hunter et al, 2011), vitelline vascular steal (Stevenson, 2021), and nicotinamide adenine dinucleotide (NAD +) deficiency (Mark, 2022). It is also possible that the etiology is heterogeneous, with several or all pathogenetic mechanisms being responsible in a subset of patients (Martinez-Frias, 1997).…”
mentioning
confidence: 99%